Luminescent Neutral Cu(I) Complexes: Synthesis, Characterization and Application in Solution-Processed OLED. (25th March 2016) - Bizzarri, Claudia; Fléchon, Charlotte; Fenwick, Oliver; Cacialli, Franco; Polo, Federico; Gálvez-López, María Dolores; Yang, Cheng-Han; Scintilla, Simone; Sun, Yinghui; Fröhlich, Roland; De Cola, Luisa
Abstract : Four novel neutral copper(I) compounds were prepared, based on the chelating phosphine bis(2-(diphenylphosphino)phenyl)ether, (DPEPhos), and a series of nitrogen-containing heterocycles as ancillary ligands. The optical properties can be tuned according to the ancillary ligand and their emissions at room temperature in aprotic solvent (CH2 Cl2 ) go from greenish blue to orange. Their photoluminescence in solid state is particularly attractive and make their employment in opto-electronic devices very appealing. In particular, the low-cost preparation method of solution-processed light emitting devices is suitable for copper(I) complexes. In order to choose a suitable device architecture, the electrochemical characteristics were investigated and the frontier orbitals values were determined. Preliminary results on solution-processed OLED are presented.